THE COMPARISON ANALYSIS OF THE EMPOWERMENT PRODUCTIVE ZAKAH BETWEEN CITY AND RURAL COMMUNITIES IN WEST KALIMANTAN PROVINCE - Kalbarini, Rahmah Yulisa; Widiastuti, Tika; Berkah, Dian (Universitas Muhammadiyah Yogyakarta, 2017)
This research purpose is to know the comparison empowerment of productive zakah between rural and urban communities in West Kalimantan Province. This research was conducted in two places, namely Lembaga Amil Zakah (LAZ) Rumah Zakah and Lembaga Amil Zakah (LAZ) Dompet Peduli Ummat. The discussion of this research is about how the comparation of productive zakah empowerment performed by LAZ Rumah Zakah to urban and LAZ Dompet Umat to rural communities in West Kalimantan Province. This research was design in the form of a qualitative descriptive research throughout case studies strategy. In this research, the researcher using observation, interview and documentation as the instruments of data collection. The researcher was interested using a pairing pattern, making of explanation and analysis of time series in technique of data analysis. Research result shows that, zakah empowerment that conducted by LAZ Rumah Zakah to urban community has fulfilled in one of the indicators which is the ability to take advantage of future enterprises. Whereas, the empowerment programs which conducted by LAZ Dompet Umat to rural community also fulfilled two indicators: the decision-making ability and economic independence. For overall, the empowerment programs which conducted by LAZ Dompet Umat is better than what LAZ Rumah Zakah did to the urban because there are two indicators achieved